2015 IEEE International Conference on Automation Science and Engineering (CASE) 2015
DOI: 10.1109/coase.2015.7294109
|View full text |Cite
|
Sign up to set email alerts
|

A real-time passive vision system for robotic arc welding

Abstract: Visual sensing in arc welding has become more and more important. However, it has remained a challenging problem due to the harsh environment, especially the interference of the extremely strong arc light. A typical industrial solution for seam detection is to use laser scanner which however still suffers from several limitations. Solutions for weld pool sensing mostly rely on high speed cameras and powerful external illuminations and therefore the wide use in industrial environments is limited. In this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The geometry parameters of the weld pool were detected by the image processing algorithm. Liu et al [27] presented a real-time passive machine vision system for weld pool sensing in robotic arc welding and proposed a detection algorithm to extract the geometrical profile of the weld pool. Since the weld pool is dynamic and its image is affected by the arc, reliable extraction of geometry parameters is a major research focus [28].…”
Section: Introductionmentioning
confidence: 99%
“…The geometry parameters of the weld pool were detected by the image processing algorithm. Liu et al [27] presented a real-time passive machine vision system for weld pool sensing in robotic arc welding and proposed a detection algorithm to extract the geometrical profile of the weld pool. Since the weld pool is dynamic and its image is affected by the arc, reliable extraction of geometry parameters is a major research focus [28].…”
Section: Introductionmentioning
confidence: 99%
“…It uses the arc light to illuminate the scene; however, this process requires an accurate calibration of the camera position and a precise selection of a narrow-band filter to reduce the arc light [7]. A few research works using passive vision have been reported to enhance and automate welding processes [8], [9], or extract different features [10]- [12] from the weld pool for gas metal arc welding (GMAW) based AM. Recent research from Zhan et al [13] introduced a method of using passive vision system for monitoring the wire deviation during the WAAM process.…”
mentioning
confidence: 99%